AB0855 Foot Involvement in Children with Juvenile Idiopathic Arthritis and Its Effect on Functional Status and Quality of Life. (15th July 2016) - Acer, S.; Bal, A.; Karaahmet, O.Z.; Başaran, Ö.; Gezer, H.H.; Acar Celikel, B.; Cakar, N.; Cakci, A.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease in children that often results in persistent and disabling foot impairments (1). Foot and ankle problems are common but relatively neglected manifestations of JIA (2). Ultrasound examination is beneficial for detecting subclinical disease, especially in foot and ankle, which are otherwise difficult to examine in children (3). Therefore, in this study, we evaluated the involvement of foot and ankle in JIA patients using both ultrasonography and physical examination. Objectives: The aim of the study was to investigate the foot and ankle involvement in JIA patients and determine the relationship between this involvement and disease activity, functional status, and quality of life. Methods: We evaluated those children who attended the Pediatric Rheumatology Department between December 2014 and April 2015. Thirty two JIA patients, aged between 6–16 years, participated in this study. Along with the demographic characteristics, the Disease Activity Score-28 (DAS-28), Childhood Health Assessment Questionnaire (CHAQ), and Pediatric Quality of Life (PEDsQoL) scores were recorded for the measurement of disease activity, physical functional status, and quality of life, respectively. The involvement of foot and ankle was investigated by both physical examination (tenderness, swelling and deformities) and detailed gray-scale ultrasonographic evaluation. Results: Of the total included JIA patients, 17 patients (53%) showed foot and ankle involvement. Foot or ankle tenderness was detected in eight patients, swelling in four patients, pes planus in four patients, calcaneal valgus in four patients, limited ankle joint range in two patients, and hallux valgus was detected in three patients. The ultrasonographic investigation revealed tenosynovitis in five patients, ankle joint effusion in four patients, synovial hypertrophy in one patient, bursitis in one patient, and plantar fasciitis in one patient. There was no difference between the group with foot and ankle involvement and the group with no such involvement in terms of demographical data or disease activity (p>0.05). A lower physical functional state was detected in the patients of the foot and ankle involvement group compared to the patients who had no such sign (p<0.05). However, this difference was not reflected in the quality of life of the patients (p>0.05). Conclusions: This study showed that foot and ankle disorders are not rare in children with JIA. Appropriate evaluation and management of the foot and ankle are important for better functional status of JIA patients. References: Spraul G. Koenning G. A descriptive study of foot problems in children with juvenile rheumatoid arthritis (JRA). Arthritis Care Res 1994;144–50. Hendry GJ. Turner DE. McColl J. Lorgelly PK. Sturrock RD. Watt GF et al. Protocol for the Foot in Juvenile Idiopathic Arthritis trial (FiJIA): a randomised controlled trial of an integrated foot care programme for foot problems in JIA. J Foot Ankle Res 2009;2:21. Hendry GJ. Gardner-Medwin J. Steultjens MP. Woodburn J. Sturrock RD. Turner DE. Frequent discordance between clinical and musculoskeletal ultrasound examinations of foot disease in juvenile idiopathic arthritis. Arthritis Care Res (Hoboken) 2012;64:4417. Disclosure of Interest: None declared